Surface modification through sustainable micro-EDM process using powder mixed bio-dielectrics. Issue 6 (26th April 2022) - Kiran, P; Mohanty, Shalini; Das, Alok Kumar
ABSTRACT: In this research, both eco-friendly and commercially available dielectric liquid (EDM oil, EDM oil + MoS2 powders (EDP), Sunflower oil (SF), and Sunflower oil + MoS2 powders (SFP)) was adopted to carry out the small area surface modification on Ti6Al4V sheet through the micro-EDM process. Brass rod (diameter: 0.95 mm) was used as the micro-tool electrode. The quality (surface roughness (Ra, Rq, Rz), recast layer (or coating) thickness (RLT), and the micro-hardness (MH)) of the coated surfaces was tested and compared with the change of input process parameters and dielectrics. The results indicate that the maximum micro-hardness of the coated layer for differently used dielectric mediums such as EDM oil, SF oil, EDP oil, and SFP oil is 495.9 HV, 619.05 HV, 665.42 HV, and 694.02 HV, respectively. Similarly, the coated layer thickness varies within the range of 4.56 to 24.42 μm (EDM oil), 7.24 to 28.31 μm (SF oil), 5.42 to 26.84 μm (EDP oil), and 4.66 to 32.75 μm (SFP oil). EDX plots suggest transfer of tool and the dielectric material (Ti, V, Al, C, Cu, Zn, Mo, S) to the substrate surface.